PENGARUH KUALITAS PRODUK DAN WORD OF MOUTH (WOM) TERHADAP KEPUTUSAN PEMBELIAN PADA USAHA PEMBUATAN BATAKO DI PT RAJAWALI SAKTI MAUMERE - Yoseph Rivaldy Lirong; Yoseph Darius Purnama Rangga; Nunsio Handrian Meylano (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2026)
The rapid expansion of the construction sector in Maumere has significantly escalated the demand for essential building materials, particularly concrete blocks. This surge has intensified market competition among local manufacturers. For a producer such as PT Rajawali Sakti, ensuring the quality of its construction materials and leveraging Word-of-Mouth (WOM) are critical strategies to influence consumer procurement decisions. This study aims to analyze the influence of product quality and WOM on the purchasing decisions of consumers of PT Rajawali Sakti’s concrete blocks in Maumere. Employing a quantitative method with a descriptive associative approach, this research collected data from 100 respondents via a Likert-scale questionnaire. The data were analyzed using multiple linear regression to determine the statistical relationships between the variables. The results indicate that product quality has a positive and significant effect on purchasing decisions. The model’s R-squared value of reveals that the combined contribution of product quality and WOM to purchasing decisions is while the remaining is influenced by external factors beyond the scope of this study. These findings provide critical managerial insights for PT Rajawali Sakti and similar construction material manufacturers, serving as an empirical basis for strategic evaluations aimed at enhancing material quality and optimizing WOM communication to improve market competitiveness and consumer adoption.